138 Differences in outcomes in neuromyelitis optica between a Japanese cohort and a predominantly Caucasian cohort from the UK. Issue 3 (9th February 2012) - Kitley, J; Leite, M I; Waters, P; McNeillis, B; Brown, R; Takai, Y; Jacob, A; Boggild, M; Nakashima, I; Vincent, A; Palace, J
Abstract : Introduction: Neuromyelitis optica (NMO) is a severe inflammatory condition causing optic neuritis (ON) and longitudinally extensive transverse myelitis (LETM). Limited forms are called NMO spectrum disorder (NMOSD). Pathogenic aquaporin-4 (AQP4) antibodies are found in most patients with NMO and some with NMOSD. Previous studies have included seronegative patients in their cohorts despite suggestions that they may behave differently. Ethnic differences have not previously been directly studied. Methods: We compared the clinical features and early long-term prognostic characteristics of 106 AQP4 antibody positive NMO/NMOSD patients from the UK (n=59) and Japan (n=47). Results: Onset age was similar in both cohorts. The majority of both cohorts experienced a relapsing course but relapse rates were higher in the UK cohort. Attacks of LETM resulted in greater disability in the UK cohort. Motor disability was greater in those with late onset disease and in Caucasians, whatever their onset symptom. Visual disability was worse in young onset patients presenting with ON. Early treatment appeared to be associated with reduced visual disability in both cohorts and reduced motor disability only in the Japanese cohort. The small number of males in the UK cohort did worse than females. Conclusion: NMO appears to be more severe in Caucasians than in Asians but outcome is also influenced by onset age, gender and treatment.